2010
DOI: 10.1090/s0002-9947-2010-04897-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between scattering matrix and spectrum of quantum graphs

Abstract: Abstract. We investigate the equivalence between spectral characteristics of the Laplace operator on a metric graph and the associated unitary scattering operator. We prove that the statistics of level spacings and moments of observations in the eigenbases coincide in the limit that all bond lengths approach a positive constant value.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 41 publications
(74 reference statements)
2
45
0
Order By: Relevance
“…The following statement is a generalisation of a result found in [5,21] that is valid for k-independent S-matrices.…”
Section: The Secular Equationsupporting
confidence: 62%
“…The following statement is a generalisation of a result found in [5,21] that is valid for k-independent S-matrices.…”
Section: The Secular Equationsupporting
confidence: 62%
“…To get an analytic handle on the nodal distribution we combine two techniques of quantum graphs analysis: the magnetic-nodal connection of Berkolaiko, Colin de Verdière and Weyand [10,19,15] and the secular manifold of Barra and Gaspard [7] further developed in [16,2,20]. We lay out the required foundations in the next subsections.…”
Section: Defining the Distributionmentioning
confidence: 99%
“…The main idea of Barra and Gaspard [7] was that if one wants to calculate the average of a certain function of the spectrum of a quantum graph, it is often possible to redefine this function in terms of the κ torus coordinates instead and then integrate over the secular manifold Σ with an appropriate measure. This idea was applied to eigenvalue statistics in the original paper [7], used to study eigenfunction statistics [16], eigenfunction scarring [20], band-gap statistics of periodic structures [2,54,26] and statistics of topological resonances [21]. Definition 3.10 (Barra-Gaspard measure [7,20]).…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…In that paper, instead of studying directly the high energy behaviour of the eigenfunctions ψn of the quantum graph, the authors study the eigenfunctions ϕjfalse(λnfalse) of associated unitary operators U(λn) which encode the classical evolution. It is shown that both notions of quantum ergodicity (for ψn or ϕjfalse(λnfalse)) are intimately related if the size of the graph goes to infinity, see also for a precise statement.…”
Section: Introductionmentioning
confidence: 99%